Water productivity and water requirements in food production - Malmquist, Louise (2018)
The majority of agricultural croplands globally is rainfed. This calls for agricultural practices which promote as productive use of precipitation water as possible, to maintain sufficient crop growth for food production. Global population is estimat-ed to increase to 9.3 billion by 2050 leading to a projected increase in food demand of 60 % from today. This, together with climate change which is projected to entail uneven precipitation patterns, will put further pressure on water resources and de-mands more thoughtful water management to maintain and improve yields.